2017
DOI: 10.1111/nep.12842
|View full text |Cite
|
Sign up to set email alerts
|

Association between responsiveness to methoxy polyethylene glycol‐epoetin beta and renal survival in patients with non‐dialysis‐dependent chronic kidney disease: A pooled analysis of individual patient‐level data from clinical trials

Abstract: Hyporesponsiveness to CERA was associated with poor renal survival, consistent with the results of the conventional erythropoiesis-stimulating agent (ESA). It is recommended that a randomized controlled trial on CERA use be performed in patients with NDD-CKD with ESA-hyporesponsive anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…There are scattered reports of poor renal [1,3,12] and life prognosis [10] in patients with NDD-CKD whose anemia does not improve sufficiently with the use of ESA preparations, although it should be noted that these studies used different definitions of ESA hyporesponders. For the CERA administered in this study, a pooled analysis of clinical trials with this drug reported that it was associated with decreased renal survival in patients with ESA hyporesponse, consistent with results with conventional ESA preparations [13]. In the trial whose dataset was analyzed here [8], there was no predominant difference in the incidence of renal prognostic events, including renal replacement therapy, between the intensive ESA treatment group and the conservative treatment groups.…”
Section: Discussionsupporting
confidence: 78%
“…There are scattered reports of poor renal [1,3,12] and life prognosis [10] in patients with NDD-CKD whose anemia does not improve sufficiently with the use of ESA preparations, although it should be noted that these studies used different definitions of ESA hyporesponders. For the CERA administered in this study, a pooled analysis of clinical trials with this drug reported that it was associated with decreased renal survival in patients with ESA hyporesponse, consistent with results with conventional ESA preparations [13]. In the trial whose dataset was analyzed here [8], there was no predominant difference in the incidence of renal prognostic events, including renal replacement therapy, between the intensive ESA treatment group and the conservative treatment groups.…”
Section: Discussionsupporting
confidence: 78%
“…They divided patients into two groups based on median erythropoietin resistance index (ERI) in Week 12 of C.E.R.A. treatment, as a measure of ESA responsiveness, and found that renal outcome (initiation of dialysis or 30% decrease in eGFR) was significantly poorer in the poor-response group compared to the good-response group [17]. Our study did not investigate ERI, but the C.E.R.A.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the observational period was only 48 weeks, and we could not evaluate the long-term outcomes and prognosis. Several studies have reported that ESA responsiveness is associated with long-term prognosis in HD patients or renal survival in CKD patients [32,33]. Hence, follow-up of these PD patients for a more extended period could provide further insights.…”
Section: Discussionmentioning
confidence: 99%